A Rare Case of Aggressive Melanotic Schwannoma Occurred in Spinal Nerve of a 59-Year-Old Male - Sung-eun Choi; Yoon Jin Cha; Jisup Kim; Hyunseo Cha; Jayeong Seo; Sung-Uk Kuh; Sung-Jun Kim; Se Hoon Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Melanotic schwannoma (MS) is a rare variant of nerve sheath neoplasm that shows ultrastructural and immunophenotypical features of Schwann cells but also has cytoplasmic melanosomes and is reactive for melanocytic markers as well. Unlike conventional schwannoma, which is totally benign, MS has an unpredictable prognosis and is thought to have low-malignant potential. Herein, we present a rare case of recurrent MS in lumbar spine of a 59-year-old male.